Evaluation of the effectiveness of the use of loans in business - Rahmonov Suhrob Ilhomovich (Open Academia, 2024)
Business loans are an important source of finance for entrepreneurs and established businesses, providing access to capital for growth, operating expenses and strategic investments. This article focuses on evaluating the effectiveness of using loans in business, and examines the opportunities they provide and the risks they may cause
Keywords: banks; credit; financial stability; growth